1996
DOI: 10.5551/jat1994.3.45
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships of Testosterone, Estradiol, Dehydroepiandrosterone-sulfate and Sex Hormone-binding Globulin to Lipid and Glucose Metabolism in Healthy Men

Abstract: We investigated the relationships of plasma sex hormones (free testosterone ; free T, estradiol ; E2, dehydroepiandrosterone-sulfate ; DHEA-S) and sex hormone-binding globulin (SHBG) levels to lipid and glucose metabolism cross-sectionally in 212 apparently healthy men aged from 18 to 59 years. A multiple linear regression analysis for lipid and glucose parameters with age, body mass index (BMI), percent body fat (%fat), waist to hip ratio (WHR), estimated maximal oxygen uptake (VO2max), alcohol and cigarette … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 55 publications
2
12
2
Order By: Relevance
“…Conversely, in the Multi-Ethnic Study of Atherosclerosis, a positive association between pre-diabetes and estradiol was reported (Colangelo et al, 2009) while two other studies reported an inverse relation between estradiol and fasting glucose (Shono et al, 1996;Dhindsa et al, 2011). When free estradiol was taken into account, we did observe a positive but non-significant association after additional adjustments for adiposity and other hormones.…”
Section: Estrogenscontrasting
confidence: 73%
“…Conversely, in the Multi-Ethnic Study of Atherosclerosis, a positive association between pre-diabetes and estradiol was reported (Colangelo et al, 2009) while two other studies reported an inverse relation between estradiol and fasting glucose (Shono et al, 1996;Dhindsa et al, 2011). When free estradiol was taken into account, we did observe a positive but non-significant association after additional adjustments for adiposity and other hormones.…”
Section: Estrogenscontrasting
confidence: 73%
“…The fact that the lipid pro®le is placed below the hormonal factor seems to indicate that obesity per se and abdominal fat distribution may induce hormonal changes and that these two factors combine to favor metabolic variations in plasma lipids. These results suggest, as do those of other authors, that fat distribution 40 and hormonal serum pro®le 41 may condition alterations in lipid metabolism in an obese population.…”
Section: Factor Analysissupporting
confidence: 71%
“…Nevertheless, several large cross-sectional studies have also shown inverse relationships of free T with BMI, the waist-to-hip ratio (WHR) or plasma insulin levels, in representative population samples of men where the vast majority had a BMI below 30. 166,167,170,212,228 ± 233 To some degree, the results from these studies may have been confounded by age, 230,232 which generally correlates negatively with free T but positively with BMI. Nevertheless, the inverse associations of free T with BMI, WHR or insulin remained statistically signi®cant in all studies where an adjustment for age was made 166,167,212,228,229,233 or where all subjects studied were within a very narrow age range.…”
Section: Physiological Mechanismsmentioning
confidence: 98%